Guaranteed‐performance consensus design for Lipschitz nonlinear multiagent systems with jointly connected topologies. (17th April 2019) - Zheng, Tang; Xi, Jianxiang; Yuan, Mei; Liu, Guangbin
Summary: Guaranteed‐performance consensualization problems for both leaderless and leader‐following multiagent systems with jointly connected topologies and Lipschitz nonlinear dynamics are investigated. To achieve the guaranteed‐performance consensus, the control protocols and quadratic performance functions based on state errors are proposed. The state error method is utilized to deal with the guaranteed‐performance consensualization problems for both leaderless and leader‐following cases. Then, the Lipschitz nonlinear problems are solved by using the Lipschitz condition. Moreover, guaranteed‐performance consensualization criteria for both leaderless and leader‐following cases with jointly connected topologies are presented in terms of linear matrix inequalities. Meanwhile, the guaranteed‐performance costs with the structure properties of both leaderless and leader‐following structures are determined. Finally, two numerical simulations are presented to verify the effectiveness of the theoretical results.